Management of surgical emergencies during the COVID-19 pandemic: a single center experience - Kallepalli, Vineel Sai Deepak; Subramanian, Jayanthan; Sanniyasi, Saravanan; Stephen, Nicole (International Surgery Journal, 2022)
Background: From the time it was declared as a pandemic by WHO, COVID-19 infection caused by corona virus (SARS-CoV-2) has drastically changed how we look at and manage patients all around the world across all faculties. Here, we wrote about a single centre experience of how surgical emergencies were managed at our institute. Methods: We have collected data retrospectively from 2019 (pre-lockdown) and 2020 (lockdown) for the months of April through July based on 281 emergency room admissions to the department of general surgery. Collected data was categorised into the two cohorts and analysed for multiple variables including days of symptoms, diagnosis arrived at, management modality being conservative or operated. Results: The most common diagnosis was found to be abscesses followed by appendicitis. Management was found to be significantly different for appendicitis in between 2019 and 2020. Other diagnosis also were analysed and found to be having an inclination towards conservative management over operative management even though the difference was not significant. The number of emergency room admissions were less in 2020 than in 2019, which was contrasting to our anticipation. On comparing with similar articles, we found that conservative management was preferred in the lockdown period, which was in concurrence with our results. Conclusions: And the patient outcome was also better when the patient was managed conservatively and taken up for surgery electively.